Anterior segment data comparison by age and gender - Ze, Ercan (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The aim of this study was to record anterior segment indices in Corum and surrounding regions and to compare these data according to age and gender. A total of 566 (265 male, 301 female) patient data sets were reviewed. Age groups were formed as group lower age (GLA) (aged 18-39 years, 140 male, 143 female) and group higher age (GHA) (aged 40-65 years, 125 male, 158 female). Evaluated indices were corneal central thickness (CCT), anterior chamber depth (ACD), anterior chamber angle (ACA), flat keratometry (K1), steep keratometry (K2) and average keratometry (Kavg). The ACD (3.71 + 0.36 mm for GLA and 3.23 + 0.44 mm for GHA), ACA (43.22 + 6.39 for GLA and 37.76 + 8.700 for GHA) and K2 (44.49 + 1.69D for GLA and 43.99 + 1.53D for GHA) results were all significantly lower in GHA compared with GLA (p<0.0001, p<0.0001 and P=0.001, respectively) Men had higher ACD values (p=0.002) than women. Women's ACAs were narrower (p<0.0001) than men. Women showed higher keratometry results as opposed to men (p<0.0001 for all). However, when gender comparison was done among GLA, there was no difference of ACD and ACA between genders. We showed our regional anterior segment results were different from other regions in the country. In addition, we showed that the significant differences of ACD and ACA did not present below the age of 40, as opposed with previous literature. It was suggested that gender combined with age gave significant differences of ACD and ACA, but not gender alone.